MA Students’ Foreign Language Learning Motivation and Autonomy in an International Learning Context - Smid, Dávid (Working Papers in Language Pedagogy, 2015)
How motivated and autonomous are tertiary-level students of English? What role does their national cultural background play in their learner profiles? Research in these areas does not seem to abound. However, since advanced learners have relatively long foreign language learning histories, they could provide valuable insights into the phenomenon in focus. This article discusses the language learning motivation and learner autonomy of MA Applied Linguistics students in Barcelona originating from a variety of countries, including Spain, China, and Japan. Its theoretical framework rests on the process model of L2 motivation (Dörnyei & Ottó, 1998). A small-scale qualitative study was carried out using retrospective interviews as an instrument for data collection. It was learned that MA students are highly motivated, committed to their goals, and possess significant learner autonomy. Different patterns emerged across the examined national cultural backgrounds in learning environment preference, management of time, concept of learner autonomy, and performance history attribution. Pedagogical implications include that university teachers of EFL should be prepared to teach in a multicultural class and promote intercultural skills.